2015
DOI: 10.1371/journal.pone.0120518
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and Morphological Analyses Reveal Phylogenetic Relationships of Stingrays Focusing on the Family Dasyatidae (Myliobatiformes)

Abstract: Elucidating the phylogenetic relationships of the current but problematic Dasyatidae (Order Myliobatiformes) was the first priority of the current study. Here, we studied three molecular gene markers of 43 species (COI gene), 33 species (ND2 gene) and 34 species (RAG1 gene) of stingrays to draft out the phylogenetic tree of the order. Nine character states were identified and used to confirm the molecularly constructed phylogenetic trees. Eight or more clades (at different hierarchical level) were identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…tortonesei , which supports the need for a taxonomic revision of the Mediterranean Dasyatidae. Such unresolved cases could be clarified by using a combined morphological and molecular phylogenetic analyses, as successfully performed for the Indo-Pacific stingrays [96]. The barcode-referenced library of voucher tissues held by ELASMOMED represents a unique opportunity for subsequent research intended to achieve taxonomic improvements.…”
Section: Discussionmentioning
confidence: 99%
“…tortonesei , which supports the need for a taxonomic revision of the Mediterranean Dasyatidae. Such unresolved cases could be clarified by using a combined morphological and molecular phylogenetic analyses, as successfully performed for the Indo-Pacific stingrays [96]. The barcode-referenced library of voucher tissues held by ELASMOMED represents a unique opportunity for subsequent research intended to achieve taxonomic improvements.…”
Section: Discussionmentioning
confidence: 99%
“…(2012), Arlyza et al (2013), and Lim, Lim, Chong, and Loh (2015) and in the sequences of four unpublished Indian H. leoparda samples (KF899500, KF899501, KF899502, and KF899353) from Indonesia, India (Bineesh), Tanzania (Zanzibar), Malaysia (Kean-Chong) and South Africa (KwaZulu-Natal, Cape Videl) were used to build the network (see Table S1). During the analysis only two base pair (bp) differences were observed between the samples in the present study and two previously-studied H. leoparda samples from South Africa [Arlyza et al (2013), H27, see Figure 1], and five bp differences observed for three H1samples from India (KF899500, KF899501, and KF899502).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there have been considerable eforts in the Asian region, with wide-ranging phylogenetic and morphological inferences [5,6], as well as the description of new species [7,11,15] and the reinstatement of a number of families [8].…”
Section: Elasmobranchs and Isheriesmentioning
confidence: 99%
“…However, the full diversity of the elasmobranchs is still unclear, and a number of species have been described in recent years, principally from the waters of Asia and Oceania [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation